Barium enema findings in total colonic aganglionosis: a single-center, retrospective study - Jiayu Yan; Jihang Sun; Rongchang Wu; Sarah Siyin Tan; Yongwei Chen; Yun Peng; Yajun Chen (BMC, 2020)
Abstract Background Preoperative diagnosis of total colonic aganglionosis is important for the rational choice of treatment. The present study aimed to evaluate the diagnostic performance of radiographic signs on preoperative barium enema in patients with total colonic aganglionosis. Methods Forty-four patients [41 (3-659) days] with total colonic aganglionosis, including 17 neonatal patients, who received preoperative barium enema at Beijing Children's Hospital, from January 2007 to December 2019 were included. All radiographs were retrospectively restudied by 2 pediatric radiologists to ascertain radiographic signs including rectosigmoid index, transition zone, irregular contraction, gas-filled small bowel, microcolon, question-mark-shaped colon and ileocecal valve reflux. Kappa test was performed to assess the accuracy and consistency of the radiographic signs. Results The 2 radiologists showed slight agreement for gas-filled small bowel, microcolon and rectosigmoid index, fair agreement for transition zone and irregular contraction, and moderate agreement for question-mark-shaped colon and ileocecal valve reflux (Kappa values, 0.043, 0.075, 0.103, 0.244, 0.397, 0.458 and 0.545, respectively). In neonatal patients, the 2 radiologists showed moderate agreement for ileocecal valve reflux and substantial agreement for question-mark-shaped colon (Kappa values, 0.469 and 0.667, respectively). In non-neonatal patients, the 2 radiologists showed substantial agreement for ileocecal valve reflux (Kappa value, 0.628). In 36 patients with total colonic aganglionosis extending to the ileum, the accuracies of question-mark-shaped colon, ileocecal valve reflux and the combination of both were 47%, 53%, and 75%, respectively, in one radiologist and 53%, 50% and 72%, respectively, in the other radiologist. Conclusions Ileocecal valve reflux is a relatively reliable radiographic sign for diagnosing total colonic aganglionosis and could improve the diagnostic accuracy upon combination with question-mark-shaped colon.